2020
DOI: 10.6027/nord2020-052
|View full text |Cite
|
Sign up to set email alerts
|

State of the Nordic Region 2020 – Wellbeing, health and digitalisation edition

Abstract: Nordic co-operation has firm traditions in politics, the economy, and culture. It plays an important role in European and international collaboration, and aims at creating a strong Nordic community in a strong Europe.Nordic co-operation seeks to safeguard Nordic and regional interests and principles in the global com-munity. Shared Nordic values help the region solidify its position as one of the world's most innovative and competitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Over recent decades, the development of eHealth solutions has increased as a response to these delivery challenges in remote areas (Roberts et al, 2010). While all the Nordic countries have national eHealth strategies with ambitious goals, the digitalisation of health and social care services proceeded relatively slowly until the onset of the COVID-19 pandemic (Lundgren et al, 2020a; see also Lundgren et al, 2020b).…”
Section: Digitalisation In Spasmentioning
confidence: 99%
See 3 more Smart Citations
“…Over recent decades, the development of eHealth solutions has increased as a response to these delivery challenges in remote areas (Roberts et al, 2010). While all the Nordic countries have national eHealth strategies with ambitious goals, the digitalisation of health and social care services proceeded relatively slowly until the onset of the COVID-19 pandemic (Lundgren et al, 2020a; see also Lundgren et al, 2020b).…”
Section: Digitalisation In Spasmentioning
confidence: 99%
“…Recent research has shown that there are several notable areas of inequality regarding health, wellbeing and living conditions, both between and within the Nordic countries. Particularly in many rural areas of the Nordic Region, the provision of welfare services is struggling to keep up with uneven demographic trends caused by an ageing population and outmigration of young people, which has, in turn, led to economic decline, recruitment difficulties and skills shortages (Lundgren et al, 2020b). The increasing proportion of older adults also gives rise to relatively high occurrences of non-communicable diseases and mental health issues in these sparsely populated areas (SPAs; Rygh and Hjortdahl, 2007;Roberts et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shrinkage is deep, firstly, because the economic downturn and deep unemployment due to structural changes has been a long time, even decades in some cases (Andreasson et al 2020;EC 2021;Makkonen et al 2022). Most are also demographically shrinking in terms of their population that are ageing and becoming increasingly centralised (Grunfelder & Roto 2013;Roto 2013;Jokinen & Cuadrado 2020). Centralisation manifests as growing urbanisation in regional centres and their surroundings, while extensive sparsely populated areas are shrinking (Helminen et al 2020).…”
Section: Introductionmentioning
confidence: 99%